Comparative analysis of quartz treated with gamma radiation originated from the hydrothermal geodes of the Paraná Basin, with quartz generated in the hydrothermal veins of Serra do Espinhaço. (Brazilian Journal of Radiation Sciences, 2021)
In Brazil, hydrothermal quartz may be found in the geodes of the basaltic rocks of the Paraná Basin and in the vein systems of quartzites of the Serra do Espinhaço. The quartz of hydrothermal origin of the Paraná Basin contains a great amount of structurally bound water in the form of molecular water, silanol, hydroxyl and abundant growth defects that are responsible for the green color formed by irradiation. To register the influence of water in the formation of the green color in the quartz of the Paraná Basin, quartz samples from the following regions were analyzed: Artigas, located in the Paraná Basin, Curvelo and Brejinho located in Serra do Espinhaço. The quartz from Artigas, formed at low temperature, has high concentration of molecular water and silanol and a greater amount of Fe than Al. The quartz from Curvelo with Al, but, without water molecular and silanol was formed by intermediate temperature and the quartz from Brejinho has very little Al, Fe and a small silanol and molecular water content. To characterize these samples, ICP, NAA, and NIR-FTIR spectroscopic measurements have been taken together with water loss techniques. The analysis by FTIR spectrometry of Artigas quartz samples shows strong absorptions of H2O and Si-OH, respectively, near the regions of 5300 cm-1 and 4500 cm-1. This content of molecular water and silanol in hydrothermal quartz of Artigas is responsible for the formation of NBOHC defects that produce, by gamma radiation, the green color.